Degradability of mulberry (Morus alba) and rice bran in the rumen of sheep fed different diets - Yulistiani, Dwi; Jelan, Z.A; Liang, J.B (Indonesian Animal Sciences Society, 2008)
The experiment was conducted to investigate degradation of dry matter (DM) and protein of mulberry and rice bran when incubated in nylon bag in the rumen at different incubation times and different rumen environments of rumen-cannulated adult sheep. Three different rumen conditions were created by feeding the three rumen-cannulated sheep with urea-treated rice straw as basal diet and offered with three supplemental treatment diets on different source of energy and nitrogen. Mulberry, urea and rice bran were used as source of fermentable energy and protein. Treatments consisted of control diet mulberry and molasses (T0); 50% mulberry was replaced by rice bran and urea (T1); and 100% of mulberry was replaced with rice bran and urea (T2). The diets were formulated in iso protein and iso energy. Supplemental diets were offered at 1.2% BW. The study was conducted in three periods. For each period, the sheep was offered with one of three supplemental treatment diets. The nylon bags each, contains sample of either mulberrry or rice bran were incubated in the rumen of sheep at different incubation times in reverse order (48, 24, 12, 9, 6, and 3h). Degradation characteristic data were obtained by analyzing degradability data with the equation of p = a+b(1-e-ct) using Neway computer package. Data of degradation characteristic, degradability of DM and CP, DMI, rumen NH3-N and pH were subjected to analysis of variance (ANOVA) using a SAS software package. The results showed that the dry matter intake (DMI) and rumen pH were not significantly different between diets. The rumen ammonia concentration of T1 and T2 was significantly higher than that of T0. However, the rumen ammonia concentration was higher than that of critical value for rumen microbial synthesis (>5mg/100ml). The rate (c value) of DM degradability of mulberry and rice bran was affected by diet treaments, where T2 diet resulted in lower c of mulberry and rice bran. Only CP degradability of mulberry on the other hand was affected by diet treatments. But, both CP mulberry and rice bran had high degradability (>80% after 24 hs incubation) in all diet treatments. It is concluded that the three diets of this study were capable of creating the optimum condition for rumen fermentation. Supplementation of mulberry or urea-rice bran mixture had similar effect on protein degradability of rice bran. On the other hand, the rate of protein degradability of mulberry was reduced when it was incubated in the rumen of sheep fed urea rice bran mix supplement. Â Â Â Key Words: Mulberry, Rice Bran, Rumen Degradability, Sheep